The effect of empathy on remote social connections via paired robots - Satoru Suzuki; Noriaki Imaoka; Takeshi Ando; Misako Uchida; Kenji Suzuki (PLoS ONE, 2025)
A range of devices and technologies are available to mediate social connections between geographically distant people. Some of these methods exploit awareness information to enhance the connectedness of distant users. However, the effect of user traits on the experience of interpersonal communication through awareness systems remains unclear. In this study, we explored the relationship between user empathy and the experience of interpersonal communication mediated by a paired robot able to convey user awareness information. We conducted an experiment to facilitate communication among distant family members using the paired robot over the course of 1 week. Participants’ empathy level and their experience of the communication were assessed using questionnaires. The findings indicated that individuals with higher empathy can better interpret their partner’s situation and feelings from the awareness information.